1986
DOI: 10.1007/bf00218069
|View full text |Cite
|
Sign up to set email alerts
|

Response of PAS-positive cells of the pituitary pars intermedia in the teleost Carassius auratus to acid water

Abstract: Summary. The PAS-positive or PIPAS cells in the pars in termedia of goldfish are activated after reduction of the pH of the ambient freshwater from 7.5 to 3.5. The cells increase in number and exhibit a five-fold increase in cell volume. Granular endoplasmic reticulum occupies most of the cytoplasm. Goldfish PIPAS cells (also termed calciumsensitive cells) are thought to have a hypercalcemic func tion. Therefore, their activation in acid water may be caused by the severe drop in plasma calcium concentration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These results show some correlation with older observations indicating the pars intermedia PAS-positive cells, previously shown to be the site of SL production (Rand-Weaver et al, 1991), to become activated during sexual maturation [quoted in Ball and Baker (1969)]. More recent histological studies have shown the PAS-positive cells to become activated in fish exposed to hypocalcaemic conditions (Olivercau ct al., 1981(Olivercau ct al., , 1985Ball et al, 1982), acidification of water (Wendelaar-Bonga et al, 1986), and dark backgrounds (van Eys, 1980; Ball & Batten, 1981). However, our studies suggest that the data concerning the PAS-positive cells and sexual maturation should be reexamined and a possible role for SL during reproduction investigated in addition to ionor coloration-controlling functions.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These results show some correlation with older observations indicating the pars intermedia PAS-positive cells, previously shown to be the site of SL production (Rand-Weaver et al, 1991), to become activated during sexual maturation [quoted in Ball and Baker (1969)]. More recent histological studies have shown the PAS-positive cells to become activated in fish exposed to hypocalcaemic conditions (Olivercau ct al., 1981(Olivercau ct al., , 1985Ball et al, 1982), acidification of water (Wendelaar-Bonga et al, 1986), and dark backgrounds (van Eys, 1980; Ball & Batten, 1981). However, our studies suggest that the data concerning the PAS-positive cells and sexual maturation should be reexamined and a possible role for SL during reproduction investigated in addition to ionor coloration-controlling functions.…”
Section: Discussionmentioning
confidence: 65%
“…0006-2960/91 /0430-1509S02.50/0 PAS-positive cells have been considered to produce a factor involved in such diverse functions as calcium regulation (Ball et al, 1982;Olivereau et al, 1985), acid-base metabolism (Wendelaar-Bonga et al, 1986), adaptation to background (Ball & Batten, 1981), and reproduction [quoted in Ball and Baker (1969)].…”
mentioning
confidence: 99%